Colonial criminology: A survey of what it means and why it is important. Issue 3 (March 2017) - King, Sanna
Abstract: As the United States is experiencing unprecedented high rates of incarceration, especially of minorities and marginalized communities, racialized punishment has been addressed by many scholars (Alexander 2010; Wacquant 2001; Cole 1999, Tonry 2011; Stevenson 2014). Studies have shown the connection between racialized structures of inequality, punishment, and colonization (Agozino 2000, 2003; Irwin and Umemoto 2016; Bosworth and Flavin 2007). However, scholars have recognized a void in the discussion of colonial theory in the field of criminology (Agozino 2003; Cunneen and Tauri 2016; Bosworth and Flavin 2007). In this paper, I identify several ways in which criminology is closely tied to colonialism. I argue that a colonial criminology perspective assists in identifying power distinctions that construct notions of difference, thus providing a more nuanced understanding of crime, violence, and criminalization as a response to oppression and alienation. I focus primarily on colonialism in Hawai'i because of its fairly recent colonization and continuing indigenous struggle for Hawaiian sovereignty. Furthermore, Hawai'i is representative of racial and ethnic inequality and disparity within the United States criminal justice system, as the majority of both the adult and juvenile incarcerated populations in Hawai'i are of Native Hawaiian and/or Pacific Islander decent.